Анализ нейросетевые методов сжатия визуальной информации - Челомбитько, А. В. (Харків: ХНУРЕ, 2011)
In this work, we consider the results of applying methods based on data compression using neural networks. We offer to conduct a comparative description of compression techniques to identify the most effective to use. Will be discussed different approaches to compression by reducing the dimension of the data and to reduce their diversity at the same dimension.
Keywords: визуальная информация; сжатие визуальной информации